2009
DOI: 10.1161/circulationaha.108.808733
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Parathyroid Hormone and the Risk of Cardiovascular Mortality in the Community

Abstract: Background-Diseases with elevated levels of parathyroid hormone (PTH) such as primary and secondary hyperparathyroidism are associated with increased incidence of cardiovascular disease and death. However, data on the prospective association between circulating PTH levels and cardiovascular mortality in the community are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
230
7
19

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(271 citation statements)
references
References 39 publications
13
230
7
19
Order By: Relevance
“…Among metabolic disorders, impaired insulin sensitivity, high prevalence of type 2 diabetes mellitus (Type 2 DM), dyslipidemia, hyperuricemia, increased body weight, and metabolic syndrome (MS) have been shown [6][7][8][9][10][11][12]. So far, it remains to be fully elucidated the pathogenetic link between PHPT and cardiometabolic morbidity and mortality which might be ascribed potentially to the contributory role of hypercalcemia, high serum PTH levels and vitamin D deficiency [4,6,13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Among metabolic disorders, impaired insulin sensitivity, high prevalence of type 2 diabetes mellitus (Type 2 DM), dyslipidemia, hyperuricemia, increased body weight, and metabolic syndrome (MS) have been shown [6][7][8][9][10][11][12]. So far, it remains to be fully elucidated the pathogenetic link between PHPT and cardiometabolic morbidity and mortality which might be ascribed potentially to the contributory role of hypercalcemia, high serum PTH levels and vitamin D deficiency [4,6,13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…These results are of particular importance when considering the crucial role of PTH for the diagnosis and treatment of bone and mineral disorders [2] and the accumulating data on PTH and cardiovascular risk [3][4][5]. With our letter we seek to guide the attention towards previous data suggesting that the renin-angiotensinaldosterone system (RAAS) may also have a significant impact on PTH levels [5][6][7][8][9].…”
mentioning
confidence: 97%
“…We therefore believe that the awareness of an interplay between PTH and aldosterone could, for selected cases, be clinically relevant for diagnostic considerations of patients with elevated levels of any of these two hormones. Apart from this, concomitant elevations of both hormones in states of either hyperparathyroidism or aldosteronism could hypothetically underlie the increased risk of mortality or cardiovascular disease associated with high PTH or aldosterone levels [2][3][4][5]16]. Whether beneficial effects of treatments of PTH or aldosterone excess are significantly mediated by an impact on both hormones warrants further studies.…”
mentioning
confidence: 99%
“…62 In a study with 958 individuals (mean age of 71 years), 617 of whom with no previous cardiovascular disease, the serum PTH level was a predictor of cardiovascular mortality, even in those with PTH values within the reference range. 6 In addition to those effects on the cardiovascular system, PTH contributes to the development of vascular calcification. An experimental study has shown that vascular endothelial cells, when stimulated with PTH, showed a reduction in the expression of the messenger RNA of osteoprotegerin, a known protection factor of vascular endothelium.…”
Section: Fgf-23: State Of the Artmentioning
confidence: 99%
“…In the past two decades, the role of P in the body has been emphasized and innumerous studies have shown the association between P and mortality, [3][4][5][6][7][8][9] suggesting that P could be a toxic element in certain circumstances. However, for many years, P has been believed not to be a deleterious factor in patients with CKD, because it remains within the reference range for a long period in the course of that disease.…”
Section: Introductionmentioning
confidence: 99%